Thriving in uncertainty: examining the relationship between perceived environmental uncertainty and corporate eco-innovation through the lens of dynamic capabilities - Han, Xiang; Yue, Beibei; He, Zhiwei (Frontiers in Environmental Science, 2023)
The impact of environmental uncertainty on firm innovation is not only influenced by the external objective environment, but also depends on the decision maker’s subjective perception. Therefore, our study investigates how entrepreneurs’ perceived environmental uncertainty (PEU) affects corporate eco-innovation in the context of small and medium-sized enterprises (SMEs) in China. Drawing on the dynamic capability view, we argue that PEU stimulates firms’ eco-innovation by enhancing their ability to sense and seize opportunities in the uncertain environment. We also examine the moderating role of government interventions, such as subsidies and official visits, in strengthening the positive relationship between PEU and eco-innovation. Using data from the China Private Enterprise Survey of 2,733 SMEs in 2016, we find empirical support for our hypotheses. Moreover, we show that firms’ dynamic capabilities mediate the effect of PEU on eco-innovation. Our study contributes to the literature on environmental uncertainty, dynamic capabilities and eco-innovation, and provides practical implications for SMEs in developing countries.